2019
DOI: 10.1021/acsami.9b02929
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Induced In Situ Manipulation of the Interlayer Coupling and Exciton Recombination in Bi2Se3/MoS2 2D Heterostructures

Abstract: 2D heterostructures are more than a sum of the parent 2D materials, but are also a product of the interlayer coupling, which can induce new properties. In this paper we present a method to tune the interlayer coupling in Bi2Se3/MoS2 2D heterostructures by regulating the oxygen presence in the atmosphere, while applying laser or thermal energy. Our data suggests the interlayer coupling is tuned through the diffusive intercalation and de-intercalation of oxygen molecules. When one layer of Bi2Se3 is grown on mon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 69 publications
(131 reference statements)
3
38
0
Order By: Relevance
“…2e shows the Raman spectra of Bi 2 Se 3 , SnS 2, and their heterostructures. The characteristic peaks of Bi 2 Se 3 near 129 and 174 cm −1 accord with the E g and A 1g vibration modes of Bi 2 Se 3 , respectively [18]. The single peak near 313 cm −1 in the spectrum of SnS 2 is consistent with the A 1g vibration mode of SnS 2 .…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…2e shows the Raman spectra of Bi 2 Se 3 , SnS 2, and their heterostructures. The characteristic peaks of Bi 2 Se 3 near 129 and 174 cm −1 accord with the E g and A 1g vibration modes of Bi 2 Se 3 , respectively [18]. The single peak near 313 cm −1 in the spectrum of SnS 2 is consistent with the A 1g vibration mode of SnS 2 .…”
Section: Resultssupporting
confidence: 63%
“…2D layered narrow-band-gap materials are outstanding heterogeneous components by virtue of their active edges, wide absorption range (up to infrared light), and high carrier mobility. For example, Bi 2 Se 3 and Bi 2 Te 3 show narrow band gaps (0.3-1.0 eV) [18,19], conductive surface states, and high specific surface areas. Furthermore, Bi 2 Se 3 and Bi 2 Te 3 are typical topologically insulator-layered materials [20,21] with an outer spinmomentum-locked Dirac cone and an internal insulating band gap [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, oxygen was also shown to be useful to control the interlayer coupling between vdW heterostructures. For example, Hennighausen et al [122] showed that impinging a low-power laser on a Bi 2 Se 3 /MoS 2 heterostructure in an oxygen-containing environment reduced the interlayer coupling effect on photoluminescence response. This is evidenced by the tunable photoluminescence (PL) spectrum whose intensity increases with increasing laser exposure time.…”
Section: Oxidation Of Metal Chalcogenidesmentioning
confidence: 99%
“…Other studies also reported fluorescence enhancement in semiconductor nanostructures doped films supported by plasmonic nanostructures. [304,305] In addition to these, other approaches like defect passivation, [306] oxygen intercalation, [307] and strain bandgap engineering [308] have also been successfully employed to enhance PL intensity. Figure 15f illustrates the deviation in PL intensity with changing polarization angle.…”
Section: Fluorescence Enhancementmentioning
confidence: 99%